1975
DOI: 10.1037/h0076810
|View full text |Cite
|
Sign up to set email alerts
|

Tonic immobility in chickens: Possible involvement of monoamines.

Abstract: Tonic immobility in chickens was affected by a variety of drugs that act on monoaminergic systems. Compounds that enhanced the duration of tonic immobility were d-LSD, BOL-148, pargyline, and iproniazid; 5-hydroxytryptophan, p-CPA, and atropine had no effect. Injections of serotonin depressed response duration. A suggestive parallel was noted between the results of the present study and those of previous work reporting druginduced suppression of raphe 1 electrical activity. The data appear to implicate monoami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Atropine, another anticholinergic which is generally regarded to have effects similar to those of scopolamine, was reported by Maser et al (1975) to have no effect on TI duration in chickens. Woodruff, Hatton, Frankl, and Meyer (1976) found decreased TI duration in ducks, but increased TI duration in guinea pigs and rabbits, using scopolamine.…”
mentioning
confidence: 99%
“…Atropine, another anticholinergic which is generally regarded to have effects similar to those of scopolamine, was reported by Maser et al (1975) to have no effect on TI duration in chickens. Woodruff, Hatton, Frankl, and Meyer (1976) found decreased TI duration in ducks, but increased TI duration in guinea pigs and rabbits, using scopolamine.…”
mentioning
confidence: 99%
“…Contradictory results regarding 5-HT and TI have also been reported. Intravenous administration of 5-HT decreased TI duration in young chickens (Maser et al, 1975) as did intracerebroventricular injections of 5-HT into rabbits (Hatton et al, 1978). The 5-HT receptor agonists, quipazine and fenfluramine, also reduced the duration of TI in chickens when injected systemically (Wallnau et al, 1981).…”
Section: Resultsmentioning
confidence: 80%
“…The possible peripheral effect of tryptophan on body temperature fosters speculation as to whether the effect of tryptophan on food intake may also be peripherally based. In an earlier study, Lacy et al (1984) found that orally administered tryptophan had no effect on tonic immobility, a behavior known to be very sensitive to brain 5-HT manipulation (Maser et al, 1975;Harston et al, 1976;Wallnau and Gallup, 1977;Hennig, 1980). It was postulated at that time that tryptophan might not be influencing food intake by increasing brain 5-HT concentrations.…”
Section: Resultsmentioning
confidence: 95%